Inequality, crime, and health among African American males - Bruce, Marino A.; Hawkins, Darnell Felix, 1946- (Research in race and ethnic relations ;, 2018)
Imprisonment, homicide, non-lethal assault and other crime, chronic and infectious disease, substance abuse, suicide, and accidents all contribute to the much wider gap in the community-level sex ratios found among African Americans compared to those observed found among other ethnic and racial groups in the United States. This wide array of causes and correlates of African American male mortality, disability, and confinement suggests an area in need of interdisciplinary inquiry that examines the intersection between public health and public safety. Health analysts and social scientists across many disciplines have studied the disproportionately high levels of disease, disability, premature death, and exposure to the criminal justice system in African Americans communities extensively. To date, there has been little overlap between the diverse literatures even though the very same factors leading to crime and punishment among African American males often contribute to their poor physical and mental health profiles. This book addresses this omission by including chapters exploring the multifaceted dimensions of the varied disadvantages faced by African American males. Authors draw from an array of theoretical and methodological frameworks to illustrate how poor outcomes and sharp disparities among individuals and communities can be linked to the interplay of multiple factors operating at multiple levels. This volume is a useful resource for serious scholars and makers of public policy who seek to understand the causal interplay among economic and racial inequality, gender, crime, punishment, and health outcomes among all African Americans.